Influence of maternity leave on exclusive breastfeeding - Fernanda R. Monteiro; Gabriela dos S. Buccini; Sônia I. Venâncio; Teresa H.M. da Costa
Abstract Objectives: To describe the profile of women with children aged under 4 months living in the Brazilian state capitals and in the Federal District according to their working status and to analyze the influence of maternity leave on exclusive breastfeeding (EBF) among working women. Methods: This was a cross-sectional study with data extracted from the II National Maternal Breastfeeding Prevalence Survey carried out in 2008. Initially, a descriptive analysis of the profile of 12,794 women was performed, according to their working status and maternity leave and the frequency of maternity leave in the Brazilian regions and capitals. The study used a multiple model to identify the influence of maternity leave on EBF interruption, including 3766 women who declared they were working and were on maternity leave at the time of the interview. The outcome assessed in the study was the interruption of the EBF, classified by the WHO. Results: Regarding the working status of the mothers, 63.4% did not work outside of their homes and among those who worked, 69.8% were on maternity leave. The largest prevalence among workers was of women older than 35 years of age, with more than 12 years of schooling, primiparous and from the Southeast and South regions. The lack of maternity leave increased by 23% the chance of EBF interruption. Conclusion: Maternity leave contributed to increase the prevalence of EBF in the Brazilian states capitals, supporting the importance of increasing the maternity leave period from four to six months.